The Translators’ Personae: Marketing Translatorial Images as Pursuit of Capital - Sela-Sheffy, Rakefet (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2008)
AbstractThis paper examines the collective self-images of Israeli literary translators, assuming that their desired idealized personae are no less effective than their actual performances in regulating the “rules of the game” in their field. In view of translators’ popular image of ‘invisibility’ and ‘submissiveness,’ my argument is that translators are compelled to make intensive use of self-promotional discourse in their endeavor to establish their profession as a distinctive source of cultural capital. The present analysis is based on around 250 profile articles and interviews, reviews, surveys of translators and other reports in the printed media from the early 1980s through 2004. Three main self-images emerge from this self-presentational discourse: (1) The translator as a custodian of language culture; (2) The translator as an ambassador of foreign cultures and an innovator, and (3) The translator as an artist in his/her own right.